IMPLEMENTASI HAK ASASI MANUSIA TENTANG PEREMPUAN DAN ANAK MENURUT HUKUM ISLAM - Qori Rizqiah H Kalingga (JURNAL JUSTIQA, 2020)
Human rights for respect must be upheld, respected and respected, there should be no SARA differences or violence with each other, instead those who are classified as weak must be protected from any actions that are contrary to their human rights. As explained in Article 1 of Law No. 39 of 1999 concerning Human Rights that human rights are a set of rights inherent in the nature and existence of humans as God's creatures and are His gifts that must be respected, highly respected and protected by the State, Law, and Government and everyone for the sake of honor and protection human dignity and dignity. In this case women and children are very vulnerable to violence and discrimination so that their rights are ignored, because women and children are considered as the weakest creatures. This phenomenon often occurs in social life due to the knowledge and understanding of people who do not understand the rights of women and children. Therefore, efforts from various parties need to be strengthened on how to provide protection and implement the rights of women and children, especially in state law and Islamic law